Crescimento e extração de nutrientes pelo abacaxizeiro cv. Vitória sob doses crescentes de micronutrientes em dois tipos coberturas do solo. - Feitosa, Hernandes de Oliveira (2010)
Foliar fertilizing has become very significant, in recent years, due to the necessity of supplying crops with micronutrients, especially crops of high economic value such as pineapple. We evaluated the vegetative performance and micronutrient absorption by the Victoria (cv) pineapple, under escalating levels of nutrients applied through foliar fertilizing and soil fertilizing and cultivated in soil covered either with waxless carnauba chaff or plastic in the climatic conditions in the Perímetro Irrigado Baixo Acaraú, state of Ceará, Brazil . We conducted two field experiments, one in soil covered with black plastic and the other in soil covered with carnauba chaff, arranged in a randomized block design in split-split plot with four levels of fertilization with FTE-12, four levels of foliar fertilization and four time intervals with five replications. The Vitória (cv) pineapple was grown in double rows spaced 0.9 m x 0.4 m x 0.3 m. The treatments applied in the plots were 0, 60, 120 and 180 kg of FTE-12 per hectare, and the tratments applied in the subplots were: T1 (no fertilization), T2 (9 foliar fertilizations using a total of 540,75 g ha-1 of Fe, 394,17 g ha-1of Mn, 182,7 g ha-1 of Zn, 150,57 g ha-1 of Cu e 100,8 g ha-1 of B), T3 (9 foliar fertilizations using a total of 1081,5 g ha- 1 of Fe, 788,34 g ha-1 of Mn, 365,4 g of Zn, 301,14 g of Cu e 201,6 g of B) and T4 (9 foliar fertilizations using a total of 2163,0 g ha-1 of Fe, 1182,51 g ha-1 of Mn, 548,1 g ha-1 of Zn, 451,71 g ha-1 of Cu e 302,4 g ha-1 of B) in the nutrient solution, taking as standard the modified Murashige and Skoog nutrient solution (1962), applied right after planting (0 days) and then 90 days, 180 days and 270 days after planting (DAP). Plant height, leaf area, plant dry matter, root dry weight, root/shoot ratio, absolute growth rate, relative growth rate, liquid assimilation rate and the leaf concentrations of Fe, Zn, Mn , and B were all evaluated in both experiments. The results showed that the applications of micronutrients did influence positively the vegetative of the plants over time, so that the highest dose of fertilizer either with FTE-12 or with foliar fertilization showed the best development at the 270th day after planting, without, however, reaching a point of maximum. In other words, the maximal doses granted higher values for the monitored plant growth variables, but did not reach a maximum point, indicating that the culture could respond positively to even higher doses of micronutrients.